Ladle and In-mold Modification Methods for Obtaining Castings from Cast Irons with Various Graphite Morphology - Zakharchenko, E.V.; Shinsky, O.I.; Baglyuk, G.A.; Klimenko, S.I.; Kurovsky, V.Ya.; Sirenko, E.A.; Goncharov, A.L. (Наука та інновації, 2019)
Introduction. In the world practice of foundry, modification has reached the status of leading direction of research and applied work to improve the technological and service properties of structural cast irons. Problem Statement. Modifying treatment of liquid iron provides for not only the creation of certain types of modifiers, but also for the development of such methods for introducing modifier into the melt, which are adaptable to the conditions of foundries and take into account the requirements for specific groups of castings. Purpose. To develop a pilot technology for the modification of electric furnace melts of cast iron in unsealed ladle with removable bowl caver and casting molds using complex reagents in the form of pressed powder briquettes and lumpy fused master alloys for the production of castings with lamellar, vermicular and spherical graphite. Materials and Methods. The following materials have been used in the research: gray cast iron, as an object of research for modifying treatment, magnesium-lanthanum-containing lumpy and briquetted powder modifiers, as well as nitrogencontaining lumpy and briquetted powder modifiers to produce cast iron with various forms of graphite, depending on the requirements for castings. Results. A pilot technology for cast irons using pressed powder nitriding briquettes to increase twice the tensile strength of structural gray cast irons (from 200 MPa to 400 MPa) without alloying and heat treatment and a ladle process for modifying molten iron melts with lanthanum-containing modifiers have been developed. The prospects for the production of nitrated iron with vermicular graphite with a sulfur content of up to 0.1% wt. by re-melting the nitrogenous metal charge and fresh and rotary cast irons and therefore with the possible minimum additional introduction of nitrogen in the furnace or in the ladle or in the mold have been substantiated. Conclusions. The pressed powder composite modifiers are recommended as the most effective ones for the mentioned modifying methods, depending on the requirements for castings. Вступ. У світовій практиці ливарного виробництва модифікування досягло статусу провідного напряму науково-дослідних та прикладних робіт з поліпшення технологічних і службових властивостей конструкційних чавунів. Проблематика. Модифікуюча обробка рідких чавунів передбачає створення не тільки певних типів модифі каторів, а й розробку таких способів введення модифікатора в розплав, які адаптовані до умов ливарних цехів, а також враховують вимоги до конкретних груп виливків. Мета. Розробка дослідної технології модифікування електропічних розплавів чавуну в негерметизованих поворотних ківшах і ливарних формах з використанням комплексних реагентів у вигляді пресованих порошкових брикетів і кускових плавлених лігатур для отримання виливків з пластинчастим, вермикулярним і кулястим графітом. Матеріали й методи. Сірий чавун як об'єкт дослідження модифікуючої обробки, магній-лантанвміщуючі кускові та брикетовані порошкові модифікатори, а також азотовмісні кускові й брикетовані порошкові модифікатори для отримання чавунів з різною формою графіту залежно від вимог до виливків. Результати. Розроблено дослідну ківшову технологію азотування чавунів з використанням пресованих порошкових азотвміщуючих брикетів, що дозволяє підвищити тимчасову розривну міцність сірих конструкційних чавунів вдвічі — з 200 МПа до 400 МПа, без легування й термічної обробки, а також розроблено ковшовий процес модифікування розплавів чавунів магній-лантанвміщуючими модифікаторами. Обґрунтовано перспективність виробництва азотованого чавуну з вермикулярним графітом з вмістом сірки до 0,1 % мас. шляхом переплавлення азотної металошихти, а також свіжих і поворотних чавунів, з мінімальним додатковим введенням азоту в піч, ківш чи ливарну форму. Висновки. Пресовані порошкові модифікатори рекомендовано до використання як найбільш ефективні для вказаних способів модифікування залежно від вимог до виливків. Введение. В мировой практике литейного производства модифицирование достигло статуса ведущего направления научно-исследовательских и прикладных работ по улучшению технологических и служебных свойств конструкционных чугунов. Проблематика. Модифицирующая обработка жидких чугунов предусматривает создание не только определенных типов модификаторов, но и разработку таких способов ввода модификатора в расплав, которые адаптированы к условиям литейных цехов, а также учитывают требования к конкретным группам отливок. Цель. Разработка опытной технологии модифицирования электропечных расплавов чугуна в негерметизированных поворотных ковшах и литейных формах с использованием комплексных реагентов в виде прессованных порошковых брикетов и кусковых плавленых лигатур для получения отливок с пластинчатым, вермикулярным и шаровидным графитом. Материалы и методы. Серый чугун, как объект исследования модифицирующей обработки, магний-лантансодержащие кусковые и брикетированные порошковые модификаторы, а также азотсодержащие кусковые и брикетированные порошковые модификаторы для получения чугунов с различной формой графита, в зависимости от предъявляемых требований к отливкам. Результаты. Разработана опытная ковшовая технология азотирования чугунов с использованием прессованных порошковых азотирующих брикетов, позволяющая повысить временную разрывную прочность серых конструкционных чугунов вдвое — с 200 МПа до 400 МПа, без легирования и термической обработки, а также разработан ковшовый процесс модифицирования расплавов чугунов лантансодержащими модификаторами. Обоснована перспективность производства азотированного чугуна с вермикулярным графитом с содержанием серы до 0.1 % масс. путем переплава азотистой металлошихты, а также свежих и возвратных чугунов, что минимизирует дополнительное введение азота в печь, ковш или литейную форму. Выводы. Прессованные порошковые модификаторы рекомендованы к использованию как наиболее эффективные для указанных способов модифицирования в зависимости от требований к отливкам.